Female, married and endorsing: integrating celebrity marital status, role congruence and credibility. (2nd January 2017) - Roy, Subhadip; Mohapatra, Subhalaxmi
Abstract: In this study, we investigate the effect of marital status and perceived role congruence (RCN) of a female celebrity endorser on consumer attitudes incorporating the role of credibility in the Indian context. The research hypotheses were tested using a series of experimental designs. The main study had a 4 (Celebrity: Unmarried/Just Married/Married but Endorsing/Married and Comeback) × 2 (Product: Role Congruent/Role Incongruent) full factorial design. Non-student samples were used in this study. Major findings implied a significant effect of celebrity marital status, RCN and the interaction term on consumer attitudes. The three source credibility dimensions were found to have differential effects on consumer attitudes when they were included as moderators. This study finds evidence in support of diminishing effectiveness of female celebrities over time/marriage. In this study, we explored a new dimension of congruence (RCN) and found the same to influence consumer attitudes favourably towards the endorsed product.